Analysis of the influence of stratum on karst development features: Taking Longtan river basin in Youyang County as an example. Issue 1 (December 2020) - Chu, X F; Yu, S; Wei, K X
Abstract: As the carrier of karst water, the stratum is capable of impacting the water yield property and karst development features, so this paper aims to find out how the stratum characteristics affect the karst water. The study site was Longtan river basin, a typical area of karst topography, located in Youyang County, Chongqing, China. Throng the statistics and analysis of the characteristics of karst water and strata, it was obvious that the thickness of strata has a significant impact on the karst water. In epi-karst, it was demonstrated that as the rock layer thickened, the flow of karst water decreased, but the number of karst springs tended to increase. The influence law was similar in deep layers, that is the relation between the stratum thickness and the average flow could be fitted by a power function, and the stratum thickness and the length of underground river, an exponential one. In addition, the flow-rate of water yielded was likely to drop fairly rapidly while the strata get deeper. Therefore, this paper successfully put forward a method, which can estimate the water resources quantity of karst water as long as the stratum thickness was available and provide a reference for the subsequent evaluation of water-abundance.